RESERVOIR CHARACTERIZATION OF CARBONATE RESERVOIRS OF BATURAJA FORMATION, KITTY FIELD, SUNDA BASIN - KUSUMA WIJAYA, ADITYA
Kitty Field is located in the southern part of Sunda Basin that produce oil from carbonate Baturaja Formation. Re-development plans and water injection program of this field, as the consequence, require detail analysis through static and dynamic approaches. This thesis focuses on the static reservoir characterization through the identification of rock type. Hence, the main goal to obtain a comprehensive understanding of the petrophysical properties of the reservoir can be achieved by identification the type, composition and rock type (RT) distribution. Based on analyses and interpretation of core and petrographic data and also seismic attribute data, carbonate of Baturaja Formation, Kitty Field is an isolated platform carbonate which divided into two depositional cycle, which are platform margin reef complex, platform interior, and shallow marine shale-basin fasies association in first cycle represented Lower Baturaja Formation and skeletal mounded fasies association in the second cycle represented Upper Baturaja Formation. RT identification is performed by FZI plot technique with the 118 routine core data. From the plot, five rock types appear, each having a very distinct porosity/permeability relationship with a high correlation coefficient. The second stage is petrographic analysis from 35 thin section samples which spread in all RT. From this analysis, RT identification is done by observation of pore types, pore sizes and pore associations based on Lucia, 1983 and Lonoy, 2006. The five RT which were identified are (1) RT 1–separate vug, (2) RT 2– separate vug intercrystalline, and interparticle micropore, (3) RT 3–separate vug (moldic micropore) and interparticle micropore, (4) RT–touching vug and interparticle macropore, dan (5) RT 5–touching vug and (fracture and channel) The formation of reservoir quality or RT from the interval study was controlled by diagenetic processes. It could be seen that generally the secondary porosity appears. The study shows that the RT is not correlated to facies. One RT appears in several facies. So the diagenetic processes becomes important in reservoir quality or rock type development. Three-dimensional reservoir characterization is performed for RT, porosity and permeability models. The modelling has been done by geostatistical approach. The study shows strong consistency between petrophysical properties and the underlying rock type models. The study results will be used as main input of dynamic simulation for water injection and further development plan in carbonate reservoir, Baturaja Formation, Kitty Field.